2007
DOI: 10.1152/ajplung.00003.2007
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-induced maturation of monocytes in preterm fetal sheep lung

Abstract: Kramer BW, Joshi SN, Moss TJ, Newnham JP, Sindelar R, Jobe AH, Kallapur SG. Endotoxin-induced maturation of monocytes in preterm fetal sheep lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 48 publications
(67 reference statements)
4
85
0
1
Order By: Relevance
“…However, 7 days after a single intra-amniotic LPS exposure, both the lung and the blood monocytes significantly increase IL6 secretion and H 2 O 2 production in response to an in vitro LPS challenge. We also recently reported that lung monocytes precociously mature to macrophages after exposure to intra-amniotic LPS (26). Thus, exposure to intra-amniotic LPS can induce maturation of monocyte function.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, 7 days after a single intra-amniotic LPS exposure, both the lung and the blood monocytes significantly increase IL6 secretion and H 2 O 2 production in response to an in vitro LPS challenge. We also recently reported that lung monocytes precociously mature to macrophages after exposure to intra-amniotic LPS (26). Thus, exposure to intra-amniotic LPS can induce maturation of monocyte function.…”
Section: Discussionmentioning
confidence: 66%
“…Cells from the suspension were then layered over discontinuous Percoll gradients (1.085 and 1.046 g/ml; Amersham Pharmacia Biotech) to separate the lung monocytic cells from the other cells. Monocytic cells were recovered from the interface between the Percoll densities (26). To obtain blood monocytes, cord blood was diluted with PBS (1/1) and layered onto a Percoll gradient as described (16).…”
Section: Lung and Blood Monocyte Isolation And Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a macrophage response was involved in the pulmonary inflammatory response to LPS in the course of gestation, shown by an increased PU.1 expression. Normally, the fetal lung contains few macrophages, and monocytes mature to macrophages with PU.1 expression after term birth (14,22,23). The lungs of fetal sheep exposed to intra-amniotic LPS expressed PU.1 within 1-2 d, and vacuolated alveolar macrophages could be recovered by lavage several days later (14).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, intra-amniotic LPS exposure induces (i) maturation of monocytes to alveolar macrophages with increased inflammatory response potentials by inducing hematopoietic transcription factor PU.1 (14) and (ii) cross-tolerance to different Toll-like receptor (TLR) agonists (15). Thus, the naive fetal immune system is capable of complex modulations that can alter subsequent immune function (13).…”
mentioning
confidence: 99%